The Calcium Sensor CBL-CIPK Is Involved in Plant's Response to Abiotic Stresses - Manik, S. M. Nuruzzaman (Int J Genomics, 2015)
Abiotic stress halts the physiological and developmental process of plant. During stress condition, CBL-CIPK complex is identified as a primary element of calcium sensor to perceive environmental signals. Recent studies established that this complex regulates downstream targets like ion channels and transporters in adverse stages conditions. Crosstalks between the CBL-CIPK complex and different abiotic stresses can extend our research area, which can improve and increase the production of genetically modified crops in response to abiotic stresses. How this complex links with environmental signals and creates adjustable circumstances under unfavorable conditions is now one of the burning issues. Diverse studies are already underway to delineate this signalling mechanism underlying different interactions. Therefore, up to date experimental results should be concisely published, thus paving the way for further research. The present review will concisely recapitulate the recent and ongoing research progress of positive ions (Mg(2+), Na(+), and K(+)), negative ions (NO(3) (−), PO(4) (−)), and hormonal signalling, which are evolving from accumulating results of analyses of CBL and CIPK loss- or gain-of-function experiments in different species along with some progress and perspectives of our works. In a word, this review will give one step forward direction for more functional studies in this area.